Punishments in Nigerian Secondary Schools: Concepts and Justifications - Jimba, Daku Noah; Joseph, Shinga Alphonsus (NIU Journal of Social Sciences, 2019)
This work titled â€œthe meaning and justification of punishment in the secondary school systemâ€ has tried to explore the concept of punishment, as different from the often mistaken understanding and meaning of discipline. Discipline connotes more of a broader concept than punishment. I t constitutes treatment to a learner, developing and training to act in accordance with rules. Although punishment inflicts some pain on the defiant, it can also be described as any intentional act used by teachers as well as parents to correct and bring back the defiant learner to a proper behaviour. The work observed that even though punishment is specific and more concrete, discipline is different and a bit abstra ct. It is the concern of the researcher to justify the fact that despite some apparent opposition of the usage of punishment, which is seen as evil within a school setting, nonetheless punishment is for the purposes of deterrence and reformation of wrongdoers within the school system. While this paper highlighted the justification of punishment to be used in the school setting to the erring learners as reformative, it is the position of the paper that punishment is an essential evil. Keywords: punishment, concept and justification